Dispersal syndromes and the use of life‐histories to predict dispersal. (11th February 2013) - Stevens, Virginie M.; Trochet, Audrey; Blanchet, Simon; Moulherat, Sylvain; Clobert, Jean; Baguette, Michel
Abstract Due to its impact on local adaptation, population functioning or range shifts, dispersal is considered a central process for population persistence and species evolution. However, measuring dispersal is complicated, which justifies the use of dispersal proxies. Although appealing, and despite its general relationship with dispersal, body size has however proven unsatisfactory as a dispersal proxy. Our hypothesis here is that, given the existence of dispersal syndromes, suites of life‐history traits may be alternative, more appropriate proxies for dispersal. We tested this idea by using butterflies as a model system. We demonstrate that different elements of the dispersal process (i.e., individual movement rates, distances, and gene flow) are correlated with different suites of life‐history traits: these various elements of dispersal form separate syndromes and must be considered real axes of a species' niche. We then showed that these syndromes allowed accurate predictions of dispersal. The use of life‐history traits improved the precision of the inferences made from wing size alone by up to five times. Such trait‐based predictions thus provided reliable dispersal inferences that can feed simulation models aiming at investigating the dynamics and evolution of butterfly populations, and possibly of other organisms, under environmental changes, to help their conservation.